Rights violation detection in multi-level digital rights management systems - Amit Sachan (2012)
Over the past few years Internet has become one of the most convenient modes of multimedia content distribution. It has provided unique opportunity for multimedia content creators and distributors. However, it has also increased the fear of illegal content copy creation and distribution. Digital Rights Management (DRM) systems emerge as one of the possible solutions to prevent illegal distribution and usage. Traditional DRM systems are two-level systems and comprise of owner and consumers as main entities. But a two-level DRM system may not provide sufficient business scalability to the owner. The owner may not be able to make proper business strategies for all regions and cultures. Thus, a multi-level DRM system containing owner, consumers, and multiple levels of distributors (e.g. distributors at national, regional and local levels) is required. However, inclusion of multiple levels of distributors in multi-level DRM systems presents several new concerns. These concerns include design of content packaging and distribution mechanism suitable for multi-level DRM system, design of suitable privacy preserving mechanisms, and design of suitable redistribution and usage rights distribution protocols. To take care of these concerns, in this thesis, we propose a multi-level DRM architecture, and present a cryptographic content packaging and distribution mechanism, privacy preserving mechanism, and redistribution and usage rights distribution mechanism. Distributors are given redistribution rights using redistribution licenses. A redistribution license is a contract between owner and distributor that defines conditions on the content redistribution by the distributor. However, a malicious distributor may violate the conditions in the redistribution licenses. So, it is necessary to detect the violations of redistribution rights. Also, multi-level DRM systems are distributed in nature so efficient violation detection mechanisms may be required. For this purpose, we propose two new license validation techniques namely, instance based validation and aggregate validation. For efficient instance based validation, we propose bit-vector transform based licenses organization and an efficient data structure using bit-vector transform. For efficient aggregate validation, we propose a prefix tree based data structure, a graph theory based algorithm, and a data structure by determining the relationship between validation inequalities used for the aggregate validation.